You Didn't Drink During Pregnancy, Did You?. (2nd February 2021) - Bakhireva, Ludmila N.; Leeman, Lawrence; Roberts, Melissa; Rodriguez, Dominique E.; Jacobson, Sandra W.
Abstract : Background: Accurate characterization of prenatal alcohol exposure (PAE) is challenging due to inconsistent use of screening questionnaires in routine prenatal care and substantial underreporting due to stigma associated with alcohol use in pregnancy. The aim of this study was to identify self‐report tools that are efficient in accurately characterizing PAE. Methods: Participants meeting eligibility criteria for mild‐to‐moderate PAE were recruited into the University of New Mexico Ethanol, Neurodevelopment, Infant and Child Health cohort ( N  = 121) and followed prospectively. Timeline follow‐back (TLFB) interviews were administered at baseline to capture alcohol use in the periconceptional period and 30 days before enrollment; reported quantity was converted to oz absolute alcohol (AA), multiplied by frequency of use and averaged across 2 TLBF calendars. The interview also included questions about timing and number of drinks at the most recent drinking episode, maximum number of drinks in a 24‐hour period since the last menstrual period, and number of drinks on "special occasions" (irrespective of whether these occurred within the TLFB reported period). Continuous measures of alcohol use were analyzed to yield the number of binge episodes by participants who consumed ≥4 drinks/occasion. The proportion of women with ≥1 binge episode was also tabulated for each type of assessment. Results: Average alcohol consumption was 0.6 ± 1.3 oz of AA/day (≈ 8.4 drinks/wk). Only 3.3% of participants reported ≥1 binge episode on the TLFB, 19.8% had ≥1 binge episode when asked about "special occasions, " and 52.1% when asked about the number of drinks the last time they drank alcohol. An even higher prevalence (89.3%) of bingeing was obtained based on the maximum number of drinks consumed in a 24‐hour period. Conclusions: Self‐reported quantity of alcohol use varies greatly based on type of questions asked. Brief targeted questions about maximum number of drinks in 24 hours and total number of drinks during the most recent drinking episode provide much higher estimates of alcohol use and thus might be less affected by self‐reporting bias. Abstract : Variability in reporting binge drinking was examined in 121 pregnant women. Only 3.3% of women reported at least one binge episode on a standard 30‐day TLFB interview in mid‐gestation. Much higher prevalence was reported when women were asked about "special occasions" (19.8%), number of drinks the last time subjects consumed alcohol (52.1%), or the largest number of drinks in 24 hours (89.3%). Participants were not asked 'since pregnancy' but were given the dates between the LMP and date of the interview.